Keeping Singapore safe: the story of the internal security department - Kumar Ramakrishna (2023)
This week marks the 75th anniversary of the founding of Singapore’s Internal Security Department, the government agency responsible for keeping the nation safe against both internal and external threats. The celebrated history of the department is outlined in this commentary to demonstrate its success from the time of its establishment, doing so with reference to the national and wider geopolitical context.